PRESENCIA DE LOS MITOS BÍBLICOS EN LA OBRA “CIEN AÑOS DE SOLEDAD” DE GABRIEL GARCÍA MÁRQUEZ (De la Crítica, 2023)
In Latin America during the 1950s, writers emerged who framed their works in magical realism. Gabriel García Maquez in Cien años de Soledad uses mythical elements, similar to biblical stories, and makes magical realism a true cultural wealth. The emblematic novel that awarded him the Nobel Prize for Literature (1982), expresses the worldview of a people and refers to many themes; one of the most recurrent is incest. This practice is narrated in several biblical passages that is why this study is relevant. The myth constitutes a positive value in the history of humanity, since it laid the foundations for the processes of understanding and interpretation of the phenomena that disturbed human thought. Not only is the myth ancient; moreover, it has been maintained over time and has enriched history. In the diversity of myths found in the Bible, the Colombian writer took some that he developed with great ingenuity and that invite the reader to evoke the biblical stories. Next, the study will focus its attention on some mythical manifestations included in the Pentateuch, that is, the first five books of the Christian Bible; namely: Genesis, Exodus, Leviticus, Numbers, and Deuteronomy. The foregoing constitutes a necessary exploration exercise of this multiform discourse that brings us closer to the world of being Caribbean.